Penerapan “Puzzle Rumah Penjumlahan” untuk Menunjang Konsep Matematika Dasar bagi Murid Slow Learner di Sekolah Dasar - Yohanis Ndapa Deda; Maria Biamsasi; Heldigardis Kolo; Hermina Disnawati; Merlina Sopbaba; Anastasia N. Ernesta Manbait (Jurnal Pengabdian Sains dan Humaniora, 2023)
The purpose of community service activities (PkM) is to strengthen the basic mathematical concepts of slow-learner students in elementary schools. The method used is a workshop in the form of mentoring. The stages of implementing this community service activity start from planning, implementing, monitoring and evaluating. The partners in this PkM activity were students at SDN Maubeli, Maubeli Village, Kefamenanu City District, North Central Timor Regency. The number of students involved was 15 people consisting of 9 female students and six male students with ages from 8 years to 10 years. There was an increase in basic math skills from the initial test of 18.44 to 50.77 on the final test. The result of this dedication shows that Puzzle Rumah Penjumlahan can be an alternative to help students learn basic mathematics. We recommend that there be research or community service that targets students who are slow in learning mathematics and students who have difficulty or are unable to learn mathematics since elementary school.